Knowledge Management Orientation and Organizational Justice as Predictors of Organizational Effectiveness of Private Colleges in Davao Del Norte - Labrado, Jayson; Moyon, Christian Paul (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined how knowledge management orientation and organizational justice influence the organizational effectiveness of private colleges in Davao del Norte. Anchored in the Knowledge-Based View (KBV) of Grant (1996) derived from the Resource-Based View (RBV) of Wernerfelt (1984), and supported by Adams’ Equity Theory and Social Exchange Theory, the research investigated how knowledge resources and perceptions of fairness contribute to institutional performance. A non-experimental quantitative design using a descriptive–correlational approach was employed to examine relationships among the variables. Data were collected from employees of private colleges in Davao del Norte using a structured survey questionnaire adapted from established instruments: the Organizational Effectiveness Scale (Kareem & Alameer, 2019), the Knowledge Management Orientation Scale (Vij & Sharma, 2004), and the Organizational Justice Scale (Purwantoro & Bagyo, 2019). Statistical analyses included mean, Pearson correlation, and multiple regression. Results indicated that knowledge management orientation, organizational justice, and organizational effectiveness were all manifested at high levels. Knowledge management orientation was characterized by strong innovation, learning, knowledge sharing, and information technology practices. Organizational justice was also highly manifested, particularly in interactional justice. Organizational effectiveness was similarly rated high across the competing values, goal, and system resource approaches. Correlation analysis revealed significant positive relationships between knowledge management orientation and organizational effectiveness (r = .821, p < .01) and between organizational justice and organizational effectiveness (r = .846, p < .01). Regression analysis further showed that knowledge management orientation and organizational justice jointly explained 75.7% of the variance in organizational effectiveness, with organizational justice demonstrating the stronger influence. The findings highlight the importance of knowledge sharing systems, innovation practices, and fair organizational processes in strengthening institutional performance. The study recommends strengthening knowledge-sharing mechanisms, enhancing transparency in management practices, and expanding professional development initiatives to sustain organizational effectiveness. This research supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting effective educational institutions and SDG 8 on Decent Work and Economic Growth through fair organizational practices and improved institutional productivity. By strengthening governance, knowledge management, and organizational fairness in higher education institutions, the study contributes to institutional sustainability, improved workforce engagement, and long-term socio-economic development in educational communities.
Keywords: Knowledge management orientation; Organizational effectiveness; Organizational justice; Private colleges; Sustainable development goals; Workplace fairness